Comprehensive aspects of taxation : finance act 1971 - Williams, Robert Glynne; Mendes, B. (London : Cassell ; St Albans : Donnington Press, Ltd., 1971)
The primary object of this book i to expand the approach to the basic principles of taxation
Earlier ed. published under title: Income tax, sur-tax and profits tax.
Includes index.
obn 24/01/2019
Loans
Keywords: Income tax; Taxation